Hlenka Regained. Irony and Ambiguity in the Narrator of Woody Allen's Another Woman - Asensio Arostegui, María del Mar (Miscelánea: A Journal of English and American Studies, 1994)
When Another Woman begins, its character-narrator Marion affirms that her life is successful and complete. Yet, as the film progresses, Marion's selfassurance is shown to be a delusion, a self-imposed mask which she has adopted in order to achieve personal, social and professional fulfilment. What I propose in this article is a narratological approach to the film that will show how it is precisely through the technique of voice-over narration, on the one hand, and through the narrator's clever use of irony and ambiguity — she spreads inconsistent and incomplete clues all through the film, transforms the process of narration itself into a source of suspense and emotion, consistently breaks the coherent temporal order of events, and constantly questions and blurs the limits between fiction and reality—, on the other, that this reversal is achieved.